OPTIMALISASI KUALITAS HIDUP PADA LANSIA MELALUI PEMERIKSAAN DAN PELAYANAN FISIOTERAPI - Antari, N.K.A. J.; Prasana, I.G.E.J.; Dewi, A.A.N.T.N.; Vittala, G. (Buletin Udayana Mengabdi; Vol 24 No 3 (2025): Buletin Udayana Mengabdi, 2024)
The Udayana Mengabdi program is created with the aim of assisting the Indonesian government's program to improve the quality of life of the elderly through physical examination and physiotherapy services for the elderly with musculoskeletal complaints and lung function, especially in the village of Tangeb, Abianbase, Mengwi, Badung. Most of the elderly in the village are still active and productive in agriculture, so there is a possibility that it will impact the health of the elderly in the village. The most common problem that arises in farmers is musculoskeletal complaints caused by errors in working positions and working duration, so musculoskeletal examinations need to be carried out. In addition, the respiratory system also has the potential to experience problems due to exposure to pesticides, so examinations of lung function also need to be conducted. By conducting physiotherapy examinations, it will provide an overview of the musculoskeletal health conditions and lung function of the elderly, so that a problem-solving solution can be carried out. The problem-solving method is carried out through community service in the form of musculoskeletal complaint examinations and lung function services, as well as physiotherapy intervention services in the form of stretching exercises and muscle strengthening exercises that will be tailored to the needs of each individual. This program will be implemented by 3 lecturers from the Physiotherapy study program and 15 students. The community service will be carried out for several days, starting from the preparation process, implementation, and evaluation of activities. Keywords: lung function, muscle problems, bone problems, elderly, physiotherapy